Cultural-led Adaptive Reuse for development of consolidated urban spaces - Chiacchiera, Francesco (Vysoké učení technické v Brně, Fakulta architektury, 2022)
As recent case studies show, the concept of Adaptive Reuse and its strategies – mainly associated to creative-led regenerations of post-industrial complexes – have been transferred to buildings and urban complexes inside the consolidated city. The analysis of recent strategies of re-activation of historical buildings and their enlarged urban context in European and International case studies shows how these reuse strategies are crucial for sustainable development of contemporary historical city centres. The analysis of emblematic and renowned case studies aims at underline architectural design strategies that make adaptive reuse of the built heritage a resource capable of generating added value for society.
Keywords: Adaptive reuse; sustainable development; refurbishment; urban re-activation; renovation